The Influence of Topography of the Pasture Area in Padang Mengatas on Biomass Composition, Biomass Production and Carrying Capacity - Marta, Yoselanda; Khalil; Mirzah (Andalasian Livestock, 2024)
This research aimed to evaluate the productivity and quality of pasture forage at BPTUHPT Padang Mengatas by analyzing the botanical composition, forage biomass production, and carrying capacity in different topographies. The research data were analyzed statistically using statistical analysis of variance using a completely randomized design with three treatments and five replications treated with three different topographies: flat, wavy, and hilly. The data obtained was processed statistically using analysis of variance. The treatment had a natural effect, so it was continued using the DMRT follow-up test. The analysis of the botanical composition of BPTUHPT Padang Mengatas pastures shows that they have many varieties of forage growing. The gramineae varieties that grow in the pastures of BPTUHPT Padang Mengatas are Brachiaria decumbens, Panicum maximum, and Cynodon plectostachyus, as well as many other types of grass, but in very low percentages. The results of statistical analysis show that differences in topography do not have a significant influence (P>0.05) on biomass production or carrying capacity in BPTUHPT Padang Mengatas pastures. From the research results, it can be concluded that there is a diversity of botanical composition in the grazing land of BPTUHPT Padang Mengatas, where Brachiaria decumbens dominates. At the same time, the average biomass production is 208 tons/ha/year.